IMAGERY DEALING WITH DEATH IN ALGERNON CHARLES SWINBURNEâ€™S â€œIN MEMORY OF WALTER SAVAGE LANDORâ€ AND â€œTHE GARDEN OF PROSERPINEâ€ - Maria Herdiana Kuncorowati; Eko Budi Setiawan (Universitas Katolik Widya Mandala Surabaya, 2017)
The research aimed to discuss imagery dealing with death in Algernon Charles Swinburneâ€™s â€œIn Memory of Walter Savage Landorâ€ and â€œGarden of Proserpineâ€. It focused on two major purposes: (1) to find out, classify and describe the imageries dealing with death in Swinburneâ€™s â€œIn Memory of Walter Savage Â Landorâ€ Â andÂ â€œThe Â Garden Â of Â Proserpineâ€. Â (2) Â to Â understand Â how Â the Â death Â is Â based Â on Swinburne description in his poem entitled â€œIn Memory of Walter Savage Landorâ€ and â€œThe Garden of Proserpineâ€. In conducting the research, some theories were used. They were theory of imagery, kinds of imagery, death, and meaning. Â Additionally, the research used two approaches. They were structural approach and formalistic approach. Furthermore, descriptive method and library research were used to finish the analysis and collecting the data. There were some visual and organic imageries which could be found in the poems. They were used to describe the bodyâ€™s condition of the dead man and what would come after death. Furthermore, there were some images of death, that is, death as eternity, freedom, and certainty. Â Keywords: imagery, death, image